PET/CT Imaging in Mouse Models of Myocardial Ischemia. (13th March 2012) - Gargiulo, Sara; Greco, Adelaide; Gramanzini, Matteo; Petretta, Maria Piera; Ferro, Adele; Larobina, Michele; Panico, Mariarosaria; Brunetti, Arturo; Cuocolo, Alberto
Abstract : Different species have been used to reproduce myocardial infarction models but in the last years mice became the animals of choice for the analysis of several diseases, due to their short life cycle and the possibility of genetic manipulation. Many techniques are currently used for cardiovascular imaging in mice, including X-ray computed tomography (CT), high-resolution ultrasound, magnetic resonance imaging, and nuclear medicine procedures. Cardiac positron emission tomography (PET) allows to examine noninvasively, on a molecular level and with high sensitivity, regional changes in myocardial perfusion, metabolism, apoptosis, inflammation, and gene expression or to measure changes in anatomical and functional parameters in heart diseases. Currently hybrid PET/CT scanners for small laboratory animals are available, where CT adds high-resolution anatomical information. This paper reviews mouse models of myocardial infarction and discusses the applications of dedicated PET/CT systems technology, including animal preparation, anesthesia, radiotracers, and images postprocessing.